2015
DOI: 10.3892/br.2015.556
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in systemic lupus erythematosus

Abstract: Abstract. Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease, with mechanisms that remain to be elucidated. Previous studies have proposed that genes and environments are required for lupus to develop and flare. It has been found that epigenetics have a significant influence on SLE. The present review will concentrate on epigenetics in SLE. There are a number of studies reporting that autoreactive T cells and B cells in patients with SLE have evidence of altered patterns of DNA methylation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
(58 reference statements)
0
11
0
1
Order By: Relevance
“…SCLE is characterized by annular or psoriasiform cutaneous lesions located above the waist (neck, trunk and outer aspect of the arms) ( 14 ). The following etiologic factors are associated with SCLE: Genetic predisposition (human leukocyte antigen-DR3); immunological factors (60% of cases are positive for total antinuclear antibodies, of which 80% of cases are associated with the presence of anti-Ro antibodies; environmental factors (exposure to ultraviolet radiation, radiotherapy, psoralen combined with ultraviolet A treatment and certain drugs, including thiazide diuretics, calcium blockers, statins, inhibitors of angiotensin converting enzyme, terbinafine and griseofulvin) ( 15 , 19 – 22 ); and an epigenetics study has reported that autoreactive T cells and B cells in patients with SCLE have evidence of altered patterns of DNA methylation, modifications of histones and microRNA) ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…SCLE is characterized by annular or psoriasiform cutaneous lesions located above the waist (neck, trunk and outer aspect of the arms) ( 14 ). The following etiologic factors are associated with SCLE: Genetic predisposition (human leukocyte antigen-DR3); immunological factors (60% of cases are positive for total antinuclear antibodies, of which 80% of cases are associated with the presence of anti-Ro antibodies; environmental factors (exposure to ultraviolet radiation, radiotherapy, psoralen combined with ultraviolet A treatment and certain drugs, including thiazide diuretics, calcium blockers, statins, inhibitors of angiotensin converting enzyme, terbinafine and griseofulvin) ( 15 , 19 – 22 ); and an epigenetics study has reported that autoreactive T cells and B cells in patients with SCLE have evidence of altered patterns of DNA methylation, modifications of histones and microRNA) ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…LN occurs in approximately 50% of SLE patients and is a major cause of morbidity and mortality in this disease [9]. Recently, several studies have provided evidence that epigenetic factors play a crucial role in the initiation and progression of the development of SLE, including LN [10]. Epigenetic factors include miRNA, methylation of DNA and acetylation of histones as well as non-histone proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between DNA methylation and other epigenetic events are briefly discussed. A detailed discussion of involved mechanisms, however, is beyond the scope of this manuscript and reviewed elsewhere [16,17].…”
mentioning
confidence: 99%